Perceptions and experiences of young Black South African women with obesity from a low socioeconomic community after following a 12-week structured exercise intervention - Phiri, Lindokuhle P.; Micklesfield, Lisa K.; Mendham, Amy E.; Goedecke, Julia H.; de Villiers, Anniza (Frontiers in Sports and Active Living, 2022)
Background Previous research has shown that Black South African (SA) women perceive a bigger body size to be acceptable and desirable, but nonetheless have shown interest in participating in community-based exercise programmes. This study aimed to investigate perceptions and experiences of participating in a 12-week exercise intervention designed to study the mechanisms of insulin sensitivity and secretion in young Black SA women with obesity. Methods Qualitative data was collected from young (23 ± 2.9 years) Black SA women (n = 17) residing in a low-income setting in Cape Town, who took part in a 12-week structured exercise intervention. Focus group discussions (FGDs) and in-depth interviews (IDIs) were conducted 1–4 months after the completion of the intervention. These were all audio recorded and took between 45 and 60 min. The recordings were transcribed, translated and qualitative content analysis, entailing a systematic process of coding and identification of salient themes, was conducted using the ATLAS.ti software. Results Six broad themes were identified from participants' experiences and perceptions: motivational factors, acceptability of the programme, barriers, sustainability and influencing others, benefits of being physically active, definitions and perceptions of exercise. Anticipated weight loss and financial remuneration were identified as motivational factors for enrolment and retention in the exercise programme. Aspects of the training environment and feelings of wellness appeared in the acceptability, sustainability and benefits themes, whereas time scheduling and travel constraints were regarded as barriers. Exercise was perceived as the maintenance of a healthy body, and in some cases, only relevant for specific groups. Conclusion Financial considerations played an important role in participants enrolling and staying in the 12-week exercise intervention. Participants liked many aspects of the intervention and identified physical and mental benefits that seemingly outweighed the barriers and disliked aspects of the programme. Optimizing the acceptability of exercise programmes and maximizing the opportunity for participants to experience improved mental well-being may contribute to attracting and retaining young Black SA women in exercise programmes.